Applied Sedimentology. - Selley, Richard C. (Elsevier, 2000)
There are three types of rockigneous, metamorphic and sedimentary. Sedimentary rocks form from the weathering, erosion, transportation and deposition of older rocks. Applied Sedimentology describes the formation, transportation and deposition of sediment, and the post-depositional processes that change soft sediment into sedimentary rock. Sedimentary rocks include sandstones, limestones and mudstones. All the world's coal, most of its water and fossil fuels, and many mineral deposits occur in sedimentary rocks. Applied Sedimentology shows how the study of sediments aids the exploration for an.